Laboratory diagnostics of alcohol intoxication in patients with alcohol-induced liver disease - A. I. Pavlov; A. I. Khazanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
Aim of investigation. To evaluate expediency of testing for carbohydrate-deficient transferrin for diagnostics of alcohol intoxication.Material and methods. For 1996-2007 overall 978 patients with liver cirrhosis (LC) were investigated, including 531 patients with alcoholic LC, 189 patients with HBV-related LC and 258 patients with HCV-related LC. One hundred and three patients taking alcohol (as two subgroups) were tested for carbohydrate-deficient transferrin – a marker of chronic alcohol intoxication. In 56 patients (54,4%) asialoglycoside transferrin was studied, in 47 (45,6%) – all spectrum of sialoglycoside transferrin deficiency: a-, mono-, bi- and three- sialotransferrin deficiency.Results. Growth of alcohol consumption by population in the country resulted in increase of number of patients with alcohol-induced LC. It account for 3,5 times more deaths (78,0%), than all viral LC. Results of these investigations demonstrated, that at testing only for asialotransferrin positive result was obtained only in 3 (5,4%) patients admitted to the hospital with severe manifestations of acute alcoholic hepatitis. At assessment of integral deficiency of transferrin, changes have been found in 36 (76,6%) patients. It confirms high diagnostic capacity of this method in testing for chronic alcohol intoxication.Conclusion. In the last decade the number of patients with alcohol-induced LC with lethal outcome essentially exceeded number of patients, died of viral LC. Assessment of integral deficiency of transferrin is highly informative method of diagnostics of chronic alcohol intoxication.